2016
DOI: 10.1002/eqe.2845
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of lateral force contribution of boundary elements in steel plate shear wall systems

Abstract: Summary Steel plate shear walls (SPSWs) are used as lateral force‐resisting systems in new and retrofitted structures in high‐seismic regions. Various international codes recommend the design of SPSWs assuming the entire lateral load to be resisted by the infill plates. Such a design procedure results in significant overstrength leading to uneconomical and inefficient use of materials. This study is focused on the estimation of contribution of boundary elements in resisting the lateral force considering their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 21 publications
1
12
0
Order By: Relevance
“…As such, an SPSW with a considerably reduced overstrength would require a lower R factor to meet the drift requirements . A few researchers investigated the contribution of the frame action to the overall strength of planar SPSWs and C‐SPSWs and reported that a modest sharing of the lateral force between the infill panel and the frame would allow for improved material efficiency. On the other hand, when a rational design procedure such as energy‐based design and displacement‐based design is used in which the design‐base shear, unlike the conventional force‐based design approach, is calculated explicitly based on the drift demands rather than using the force modification factors, reducing unnecessary overstrength can improve the design economy.…”
Section: Plastic Analysis and Efficient Designmentioning
confidence: 99%
“…As such, an SPSW with a considerably reduced overstrength would require a lower R factor to meet the drift requirements . A few researchers investigated the contribution of the frame action to the overall strength of planar SPSWs and C‐SPSWs and reported that a modest sharing of the lateral force between the infill panel and the frame would allow for improved material efficiency. On the other hand, when a rational design procedure such as energy‐based design and displacement‐based design is used in which the design‐base shear, unlike the conventional force‐based design approach, is calculated explicitly based on the drift demands rather than using the force modification factors, reducing unnecessary overstrength can improve the design economy.…”
Section: Plastic Analysis and Efficient Designmentioning
confidence: 99%
“…However, recent researches pointed out that the boundary column would be carried large additional forces that were transmitted from SPSW or CSPSW once tension field was formed in them . Such phenomenon may result in a great impact to the boundary column, thus strong columns must be used to prevent potential collapse of the structure due to the large forces .…”
Section: Introductionmentioning
confidence: 99%
“…[9,10] Thus, many researches were conducted to investigate the seismic performance of CSPSW in experimentally and numerically.However, recent researches pointed out that the boundary column would be carried large additional forces that were transmitted from SPSW or CSPSW once tension field was formed in them. [11][12][13] Such phenomenon may result in a great impact to the boundary column, thus strong columns must be used to prevent potential collapse of the structure due to the large forces. [14] Thus, many important researches were conducted…”
mentioning
confidence: 99%
“…Horizontal boundary elements are designed to restrict the formation of plastic hinges at the two ends, whereas it is desired that vertical boundary elements (VBEs) essentially remain elastic under the Design‐basis Earthquake (DBE) hazard level. Stiff and elastic VBEs ensure the better drift distribution and reduce the possibility of formation of soft‐storey mechanism in SPSWs …”
Section: Introductionmentioning
confidence: 99%
“…Stiff and elastic VBEs ensure the better drift distribution and reduce the possibility of formation of soft-storey mechanism in SPSWs. 8,9 Steel plate shear walls in high-rise buildings usually experience high overturning moment demand under lateral loading. This leads to high axial force demand on the VBEs, resulting in the unreasonably high cross-sectional requirements.…”
Section: Introductionmentioning
confidence: 99%